Advanced strategies for production of soy-processing enzyme - Islam, S. M. Mahfuzul; Ju, Lu-Kwang (Frontiers in Bioengineering and Biotechnology, 2023)
Enzyme production is critical and often costly for biorefinery. It is challenging to produce enzymes with not only high titers but also proper combinations of all required activities in a single fermentation. This work aimed at improving productivity and composition of the multiple enzyme activities required for hydrolysis of complex soybean carbohydrate in a single fermentation. A previously selected Aspergillus niger strain was used for its high carbohydrases and low protease production. Strategies of fed-batch substrate addition and programmed pH-decrease rates were evaluated. Cheap soybean hull (SH) was confirmed to induce production of all necessary carbohydrases. Surprisingly, fed-batch SH addition, originally thought to sustain substrate-inducer availability and reduce feedback repression by sugars, did not increase pectinase and cellulase production significantly and even lowered the α-galactosidase production, when compared with batch fermentation having the same total SH amount (all added initially). On the other hand, the pH-decrease rate could be effectively optimized for production of complex enzyme mixtures. The best fermentation was programmed to lower pH from 7 to 4 in 84 h, at a drop rate of .0357 per h. It produced the highest pectinase (19.1 ± .04 U/mL), α-galactosidase (15.7 ± .4 U/mL), and cellulase (.88 ± .06 FPU/mL). Producing these high enzyme activities in a single fermentation significantly improves the effectiveness and economics of enzymatic soy processing, which, e.g., can hydrolyze the 30%–35% carbohydrate in soybean meal to sugars, with minimal protein degradation, to generate high-value protein-rich products and a hydrolysate as fermentation feedstock.